The Influence Of Creative Projects Through Entrepreneurship Education On Entrepreneurial Motivation In Vocational High School Students: A Systematic Literature Review - Sugihartono, Agus; Indah K, Luluk Nur; Wati, Andi Prasetyo; Murwani, Fulgentius Danardana; Wardana, Ludi Wishnu (Journal of Applied Business, Taxation and Economics Research, 2024)
The development of Vocational School Creative and Entrepreneurship Projects (PKK) is expected to produce graduates who can produce products and services that are needed by society while also having economic value. Therefore, PKK learning in vocational schools has an important role in preparing graduates to be ready to enter the world of work through entrepreneurship as well as being a preferred path to employment. The (SLR) method is used to compile this scientific article. About research methods: "Literature" refers to the critical analysis of ongoing research on a particular subject or in the form of scientific questions helps us build a mentality that is consistent with theories, findings, and previous research results to complete the problem formulation of this review. This research aims to study PKK subjects and hopefully be able to serve as a guide for 1. Vocational school education units in implementing PKK subject learning; 2. Vocational School Education Unit in developing and managing human resources, infrastructure, and equipment; 3. Educators and students in implementing PKK subjects who can become entrepreneurs. Learning Creative Products and Entrepreneurship, apart from that, in the Business Opportunities material, students can assess the existence of opportunities for business according to their respective skill competencies, students can provide ideas for their work in the form of innovative and creative products. In implementation, it is very effective and enjoyable for students, because it can develop students' abilities, while the teacher is a facilitator, according to the syntax in project-based learning where students are directed to create projects/products, starting from pre-scheduled planning to reporting results to the teacher.